Global efficiency estimation method of complex network based on fractal property - Sheng ZHANG; Weikai DAI; Feng WU; Wenxiang LAN (Tongxin xuebao)
A method of network efficiency estimation based on fractal property was proposed for solving the problems of high complexity and time-consuming calculation of efficiency in large scale networks.Considering the fractal properties of complex network topology,the relationship between network efficiency and node correlation sum was analyzed,and the global network efficiency was estimated by partial nodes.Besides,to rapidly find the fractal properties of complex networks,a fractal property discrimination method based on node correlation sum was proposed.The experimental analysis in the construction network and the real-world network show that the proposed method can accurately and effectively estimate the global efficiency of the network,which reduces the calculation time by at least 90% compared with the original method.